تحليل اختبار الكفاءة اللغوية في أسئلة الاختبار النهائي لصف الثامن بمدرسة المتوسطة الحكومية الثانية بورواكارتا - Hasyim, Ainun; Sanah, Siti (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
This linguistic competency test is very important in evaluation Arabic language learning .even though this test does not measure students practical language skills linguistic competency is a prerequisite for language activities. This research aims to determine the patterns of linguistic competency tests and cognitive level of the test the methode use this research is descriptive qualitative with a content analysis approach this research was carried out MTsN 2 purwakarta ,while documentation techniques were used to collect research data the result of the research show a variety of competency test patterns syntax tests with i`rab arrange words into the number of ismiyah or fiiliyah.the clarification test is by determining the meaning and the formation test is by completing the sentence with the right words the cognitive test level is dominated by LOTS ( Low Order Thinking skill ) with 37questions and 8 question for the HOST ( High Order Skill Thinking Skill) category,thus research provides a wide range of references for teachers in preparing Arabic language question